2021
DOI: 10.3390/antibiotics10010075
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterization of Coagulase Positive Staphylococci from Food Products and Human Specimens in Egypt

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) strains have veterinary and public health importance as they are responsible for a wide range of difficult to treat infections and food poisoning. Two hundred samples (50 samples each of minced meat, beef luncheon, Karish cheese, and human samples (pus swab from open wounds)) were cultured, and MRSA strains were identified using disk diffusion tests and mecA gene-based PCR. A total of 35% (70/200) of the examined samples were confirmed as coagulase-positive S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Staphylococcus aureus is one of the most common causes of infections and it's also a normal flora of skin that can enter the body through abrasion, cracks, burn, surgical incisions, cuts and causes pyogenic infections (Sangita et al 2019). This study has revealed that S. aureus is the most predominant micro-organism from pus samples, as earlier studies have indicated (Onemu and Ophori 2013), with the occurrence of 72.7% which is almost similar to the finding in the study conducted in Algeria 64.28 % (Benyagoub et al 2020), but its higher than results obtained in Egypt 38% (Abdeen et al 2021) and in Maroc 19% (Benouda and Elhamzaui 2009). For S. epidermidis the highest occurrence was identified from urine with the rate of 91.4%, probably this is primarily related to the contamination of urine by the commensal flora (Frédéric et al 2008), and according to Longauerova (2006) 2 show the variation of the prevalence of S. epidermidis and S. aureus according to the gender of patients.…”
Section: Resultssupporting
confidence: 87%
“…Staphylococcus aureus is one of the most common causes of infections and it's also a normal flora of skin that can enter the body through abrasion, cracks, burn, surgical incisions, cuts and causes pyogenic infections (Sangita et al 2019). This study has revealed that S. aureus is the most predominant micro-organism from pus samples, as earlier studies have indicated (Onemu and Ophori 2013), with the occurrence of 72.7% which is almost similar to the finding in the study conducted in Algeria 64.28 % (Benyagoub et al 2020), but its higher than results obtained in Egypt 38% (Abdeen et al 2021) and in Maroc 19% (Benouda and Elhamzaui 2009). For S. epidermidis the highest occurrence was identified from urine with the rate of 91.4%, probably this is primarily related to the contamination of urine by the commensal flora (Frédéric et al 2008), and according to Longauerova (2006) 2 show the variation of the prevalence of S. epidermidis and S. aureus according to the gender of patients.…”
Section: Resultssupporting
confidence: 87%
“…Among MDR patterns, CD-E-TE, standing for clindamycin, erythromycin, and tetracycline, was displayed in most of the isolates (34.2 %), and the pattern is identical for humans, chickens, and rodents. Different studies on the resistance profiles of S. aureus have reported similar patterns as well [7,18,32,33,39,40]. Erythromycin and tetracycline are the most commonly used antibiotics in this area, since they are cheap and can be purchased over the counter without a prescription [41].…”
Section: Discussionmentioning
confidence: 78%
“…A previous study employing the 16S rRNA genes sequencing and microarray analysis revealed six clonal complexes of S. aureus recovered from household cattle and buffaloes in Egypt [54]. Analysis of the mecA gene sequences of S. aureus obtained from different food products and human pus samples reported high nucleotide similarities between the S. aureus strains from different origins [53]. Another genotyping assay using the Staphylococcal protein A (spa) gene sequences of S. aureus strains isolated from cattle and camels in Egypt revealed the presence of eight SPA types; the most common SPA type was t359 that found in five isolates of S. aureus [55].…”
Section: Discussionmentioning
confidence: 94%
“…Several Egyptian and global studies performed the comparative sequence analysis of S. aureus isolated from bovine subclinical mastitis and various food sources [16,[51][52][53]. A previous study employing the 16S rRNA genes sequencing and microarray analysis revealed six clonal complexes of S. aureus recovered from household cattle and buffaloes in Egypt [54].…”
Section: Discussionmentioning
confidence: 99%